Cytochalasins from the Ash Endophytic Fungus Nemania diffusa DSM 116299 - Özge Demir; Katharina Schmidt; Barbara Schulz; Theresia E. B. Stradal; Frank Surup (Molecules)
The secondary metabolome of Nemania diffusa, isolated as an ash endophytic fungus, was analyzed in detail. From its cultures, a previously undescribed cytochalasin 1 was isolated using preparative HPLC, together with six known congeners: 18-dehydroxy-cytochalasin E (2), cytochalasins Z7 (3), Z8 (4), and E (5), 18-dehydroxy-17-didehydro-cytochalasin E (6), and K Steyn (7). The structures of these compounds were determined using data from high-resolution mass spectrometry (HR-MS), in combination with 1D and 2D nuclear magnetic resonance (NMR) spectroscopy. Metabolites 1–4 share a characteristic 12-membered lactone moiety, placing them within a rarely examined cytochalasin subclass. Thus, the compounds were incorporated into our ongoing screening campaign to study the structure–activity relationship of this metabolite family. We initially determined their cytotoxicity in eukaryotic mouse fibroblast L929 cells using an MTT-based colorimetric assay, and further investigated their effect on the cellular actin dynamics of the human osteosarcoma cell line U-2OS in detail. Unexpectedly, we discovered a high number of irreversible compounds (1, 2, and 4). Additionally, we highlighted specific structural features within the 12-membered cytochalasin subclass that may play a role in directing the reversibility of these compounds.